Benznidazol livre e nanoestruturado na terapia da Doença de Chagas experimental e seus efeitos sobre biomarcadores do sistema colinérgico e estresse oxidativo - Silva, Aniélen Dutra da (2022)
Chagas disease (CD) is widely distributed in Latin America, caused by Trypanosoma cruzi. The infection promotes an inflammatory process, which triggers several factors of the immune response. The cholinergic system acts in the modulation of the inflammatory response, through the anti-inflammatory cholinergic pathway. In Brazil, the treatment of CD is done with the drug benznidazole (BNZ), which has adverse effects and high toxicity. The use of biotechnology is an ally in the search for strategies in the development of forms of drug administration with greater efficiency and less damage to the body. The objective of this study was to understand the participation of the cholinergic system in the pathogenesis of the disease and bring new possibilities in the treatment, as well as interactions between treatments and cholinergic signaling in immune regulation. Three experimental protocols were carried out, through which the performance of the cholinergic system during CD, efficacy tests of free drug (BNZ) and nanostructured (NBNZ) at different doses were analyzed, in addition to evaluating treatments in CD therapy and their effects. on hematological, biochemical, oxidative and pathological stress parameters and on the cholinergic system. It was possible to demonstrate that the cholinergic system may be involved in immunomodulation during infection, as there was a reduction in acetylcholinesterase activity in the central nervous system, as well as an increase in acetylcholine levels, characterizing an anti-inflammatory response. The efficiency of the benznidazole nanoencapsulation process in CD therapy was demonstrated. The 20 mg/kg NBNZ dose showed a significant reduction in parasitemia, similar to the free drug. In addition, low cytotoxicity, reduced tissue damage and increased survival rate compared to other doses of nanocapsules (5mg/kg, 10mg/kg, 15mg/kg). Thus, the 20 mg/kg NBNZ dose showed better performance in the analyzes performed. It was also possible to observe that the BNZ nanoencapsulation process, despite promoting a reduction in parasitemia, did not demonstrate greater efficacy than the treatment with BNZ. T. cruzi infection caused anemia, leukopenia and thrombocytopenia in the animals, but treatment with BNZ was able to prevent this change. On the other hand, all infected treatment groups showed changes in biochemical markers of liver damage. The evaluation of the anti-inflammatory cholinergic pathway showed a pro-inflammatory profile through the evaluation of AChE activity, AChE expression, and M1 and M2 mAChR receptors in lymphocytes, this profile was observed in the infected group treated with BNZ, demonstrating that the drug acts by stimulating this pro-inflammatory signaling pathway. When evaluating the oxidant/antioxidant status, a pro-oxidant pattern was observed in the evaluated tissues, mainly in the levels of ROS and NOx of the treated groups, important molecules in the control of parasite proliferation in the acute phase of the disease. In general, we concluded that nanoencapsulation did not potentiate the therapeutic efficacy of benznidazole, but minimized pathological changes caused by T. cruzi infection and that the cholinergic system presents itself as a potential pharmacological target for the control of the inflammatory process and the evolution of damage caused by the infection.